TINJAUAN HUKUM TANGGUNG JAWAB DEVELOPER TERHADAP PEMENUHAN HAK KONSUMEN PERUMAHAN - Karmila Karmila (Lakidende Law Review, 2022)
The form of implementation of the developer's responsibility towards fulfilling the rights of BTN housing consumers are as follows: the right to obtain information, the right to obtain good housing construction, the right to obtain public facilities provided directly by the developer and the right to obtain insurance coverage. The settlement efforts taken by the consumer and business actors in resolving the problems faced by the consumer are carried out through non-litigation or amicable legal settlements carried out by both parties. This research uses the type of empirical normative research. The type of normative research is a type of research that emphasizes the study of legal science and seeks to examine the applicable legal rules. The results in this study are the form of implementing the developer's responsibility for fulfilling the rights of BTN housing consumers as follows: the right to obtain information, the right to obtain good housing construction, the right to obtain public facilities provided directly by the developer and the right to obtain insurance coverage.